COMMUNITY-BASED WASTE MANAGEMENT: A STUDY OF COMMUNITY PARTICIPATION FROM THE PERIPHERY OF BANYUMAS DISTRICT - Rahmawati, Isna; Pratiwi, Anggita Bunga (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Household waste management through waste banks is an effort made by the community to reduce the volume of waste in landfills. Household waste management is very important to solve the increasingly complex waste problem. Community participation is the main key because the community is the actor in waste management activities. This study aims to examine community participation in the stages of waste management at the Inyong waste bank in Banyumas Regency. The approach applied in this research is qualitative with descriptive analysis method. The data used came from two sources, namely primary and secondary data, with data collection techniques through observation, interviews and literature studies. The research data were analyzed through data reduction, data presentation, and verification and conclusion drawing. The informants in this study were the management and customers of the Inyong waste bank. The results showed that the community participated in waste management activities in Inyong waste bank starting from the planning, implementation, evaluation, and utilization stages. However, efforts to increase community participation in the evaluation stage need to be made by holding special meetings held to evaluate the waste management program periodically.